BLACK BOX TESTING USING EQUIVALENCE PARTITIONING TECHNIQUE ON BAKKAR WEBSITE - Aisya Tyanafisya; Algyon Faras; Nakula Bintang Nashwandra; Reza Pratama; Raisa Mutia Thahir; Wicaksono, Aditya; Mindara, Gema Parasti (Department of Informatics Engineering, Faculty of Science and Technology, Universitas Islam Negeri Alauddin, Makassar, Indonesia, 2025)
This study aims to evaluate the functionality of the Bakkar website using the Black Box Testing method and the Equivalence Partitioning technique. The primary focus of testing lies in the login and registration features, which are critical components of user interaction. Equivalence Partitioning was employed to divide input data into valid and invalid partitions, allowing for efficient test case coverage without sacrificing thoroughness. In total, 17 test scenarios were designed to represent various user input conditions. The results showed that 15 out of 17 test cases were executed successfully, resulting in a success rate of 88.24%. The two failed scenarios revealed that the system lacked clear feedback when handling invalid inputs, such as incorrectly formatted emails or insufficient password length. These outcomes highlight the need for better input validation and more informative error messages to improve system reliability and user experience. Overall, the findings demonstrate that the Equivalence Partitioning technique is effective for identifying functional issues in web applications and can be a practical approach for similar testing contexts.